1992
DOI: 10.1111/j.0022-3646.1992.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE PHYSIOLOGY AND BIOCHEMISTRY AND TAXONOMIC ASSIGNMENT OF THE CHLORELLA (CHLOROPHYCEAE) STRAINS OF THE CULTURE COLLECTION OF THE UNIVERSITY OF TEXAS AT AUSTIN1

Abstract: The species of the genus Chlorella exhibit considerable biochemical and physiological differences. Therefore, it is important to select for and utilize in research or biotechnology correctly identified strains of the species having the most favorable properties for the respective project. We examined the Chlorella strains of the University of Texas collection at Austin, Texas, according to species‐specific chemotaxonomic characters and assigned 58 strains to 10 well‐established species (only 17 of these strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 17 publications
2
40
0
1
Order By: Relevance
“…However, the lack of distinctive morphological features and the asexual reproduction of these algae caused considerable problems in taxonomic descriptions and classification (Kessler & Huss, 1992). In a biochemical and phylogenetic study, Chlorella species were found to be distributed in two classes of green algae, the Trebouxiophyceae and the Chlorophyceae (Huss et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of distinctive morphological features and the asexual reproduction of these algae caused considerable problems in taxonomic descriptions and classification (Kessler & Huss, 1992). In a biochemical and phylogenetic study, Chlorella species were found to be distributed in two classes of green algae, the Trebouxiophyceae and the Chlorophyceae (Huss et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although members of the genus suffer from a scarcity of morphological characters, more than 100 Chlorella species have been named since the description of the type species Chlorella vulgaris Beijerinck in 1890. These taxa have been described from freshwater, marine, and edaphic habitats or as endosymbionts (komárek & Fott 1983;huss et al 1989;nishihara et al 1998;hoshina et al 2005;summerer et al 2008;Škaloud 2009;khayBullina et al 2010;Pröschold et al 2011). Over time, numerous studies aimed at revising the systematics of this genus have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The first monograph of Fott and Novakova, [6] based on morphological features, established the nomenclatural types, but also showed the phenotypic plasticity of the investigated species. Physiological, biochemical and molecular phylogenetic investigations of Kessler, [16] Kessler and Huss, [17] and Huss et al [7] made evident that the genus Chlorella consisted of a taxonomically heterogenous complex and its species were dispersed among two classes: Trebouxiophyceae and Chlorophyceae. [18] The studies of the cell wall's chemical composition by Takeda [19,20] allowed him to group Chlorella species into two clusters: a glucosamine-type group and a glucantype group.…”
Section: Resultsmentioning
confidence: 99%